Sensitivity analysis of the SMARTER and MOORA methods in decision making of achieving students - Intan Nur Farida; Umi Mahdiyah; Akbar Fastio Hari Setiawan (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Evaluation of student learning in Islamic boarding schools is still limited to the results of exams conducted in writing which can lead to the determination of student achievement using simple criteria, resulting in less than optimal results. In addition, the importance of selecting criteria to suit the learning characteristics of the Islamic boarding school students. The purpose of this study is to assist the process of evaluating student learning based on the value of the criteria, sub-criteria, and priorities. The method used is Rank Order Centroid in assigning weight values ​​to the criteria applied to the Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) and Multi-Objective Optimization By Ratio Analysis (MOORA) methods. This study produces the same alternative value in the first rank. To calculate the accuracy is done by using sensitivity analysis according to the results of preference values ​​in each method. Based on the sensitivity analysis shows that in the first sensitivity calculation the lowest value is obtained. The sensitivity value of the SMARTER method on the first sensitivity is 0.0714. While the first sensitivity value of the MOORA method is 0.0076. So the best method is owned by the MOORA method because it has the lowest sensitivity value.